Knowledge and Attitudes Regarding Human Papillomavirus Vaccination Among Future Healthcare Workers in Serbia - Nemanja Maletin; Nikola Denda; Ana Ljubičić; Radmila Velicki; Aleksandra Patić; Zoran Golušin; Tihomir Dugandžija; Vladimir Petrović; Mioljub Ristić; Vladimir Vuković (Vaccines)
Background/Objectives: Adequate knowledge and correct attitudes about the HPV vaccine influence awareness of the importance of preventing HPV-related diseases, which is particularly important for future healthcare professionals. We aim to examine the share of correct answers and the prevalence of different attitudes about the HPV vaccine among active regular students of the Faculty of Medicine in Novi Sad. Methods: A cross-sectional study was conducted from 1 to 30 November 2023 using a structured survey questionnaire. Results: A total of 1760 students were included, of which 78% were female, with an average age of 21 years. Students who participated in prior HPV education) demonstrated significantly higher knowledge (81.92% vs. 65.60%, p < 0.001) and were more likely to recommend the vaccine to patients (89.91% vs. 82.99%, p < 0.001). Almost all vaccinated students (99.41%) would recommend the vaccine, compared to 82.91% of unvaccinated students (p < 0.001). Students who actively sought HPV information also showed a higher likelihood of recommending the vaccine (93.05% vs. 83.02%, p < 0.001). Moreover, those with sufficient self-assessed knowledge were more inclined to recommend the vaccine (89.88%) than those with insufficient knowledge (81.66%, p < 0.001). The analysis demonstrated that an increase in the number of correct answers in the knowledge evaluation corresponds to higher odds of recommending the HPV vaccine to patients (OR = 1.23, 95% CI 1.17–1.28). Positive attitudes prevailed, with 68.89% supporting more education on HPV vaccination. Conclusions: Students who previously attended education on HPV infection/vaccination and those who would recommend the vaccine have significantly higher levels of knowledge. The study highlights the importance of HPV-related education in shaping future healthcare professionals’ attitudes and knowledge.